A non-dispersive instrument using the solar occultation flux method for gas emissions from volcanoes and industries - Beecken, Jörg; Borgentun, Carl (My University, 2007)
Volcanoes and industries are well known emission sources for gases affecting the environment. It is of environmental, geochemical and public interest to quantify these emissions. The aim was to extend already known techniques with a new, smaller, more robust, and inexpensive instrument. The instrument was developed to be applicable in connection with the solar occultation flux (SOF) method. The method makes use of the molecular absorption of infrared light in the atmosphere using the Sun as a background source and information about the wind speed to determine the amount of emission in terms of mass per time. The instruments which were usually used to measure the column density of the gases are highly sophisticated, comparatively huge and expensive. Two basic techniques are applied to realize this instrument depending on its application for measurements of emissions from industries or volcanoes. The industries, especially petrochemical industries and refineries, emit a high amount of alkanes. Due to their broad absorption features in the infrared broadband radiometry is used to measure their column density. In the volcanic application hydrogen chloride and hydrogen fluoride are of high interest. They have very narrow absorption features, thus gas correlation spectroscopy is applied in this instrument to quantify their amount. To find suitable bandpass filters for the broadband radiometry application a software (qesof) was used to simulate their behaviour. Other simulations based on the HITRAN database were conducted to find appropriate parameters for the gas cells and bandpass filters used for the gas correlation spectroscopy application. The instrument was designed, built and with good results tested in the laboratory.
Keywords: Molekylfysik; Optik; Optisk fysik; Elektronisk mät- och apparatteknik; Molecular physics; Optics; Optical physics; Electronic measurement and instrumentation